2014
DOI: 10.1177/0165551514534143
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effects of preprocessing strategies on sentiment analysis for Arabic text

Abstract: Sentiment analysis has drawn considerable interest among researchers owing to the realization of its fascinating commercial and business benefits. This paper deals with sentiment analysis in Arabic text from three perspectives. First, several alternatives of text representation were investigated. In particular, the effects of stemming, feature correlation and n-gram models for Arabic text on sentiment analysis were investigated. Second, the behaviour of three classifiers, namely, SVM, Naive Bayes, and K-neares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 16 publications
1
93
0
2
Order By: Relevance
“…Duwairi and El-Orfali [26] performed a study on SA for Arabic text. e authors used two datasets: one prepared inhouse related to politics domain and the other prepared by Rushdi-Saleh et al [8] related to movie domain.…”
Section: Discussion and Future Research Avenuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Duwairi and El-Orfali [26] performed a study on SA for Arabic text. e authors used two datasets: one prepared inhouse related to politics domain and the other prepared by Rushdi-Saleh et al [8] related to movie domain.…”
Section: Discussion and Future Research Avenuesmentioning
confidence: 99%
“…Preprocessing [17] Normalization, POS tagging [24][25][26][27] Stemming [28][29][30][31][32][33] Text cleaning [34][35][36][37][38][39] Normalization, stemming, stop words removal [40][41][42] Text cleaning, normalization, stemming, stop words removal [43][44][45] Normalization Text cleaning, normalization, tokenization, stemming, stop words removal [49][50][51][52] Normalization, tokenization [53,54] Text cleaning, normalization, tokenization [55,56] Normalization, tokenization, POS tagging [13,[57][58][59][60][61][62][63][64] Normalization, tokenization, stemming, stop words removal [65,66] Normalization, tokenization, stemming, lemmatization [67,68] Text cleaning, normalization, tokenization, stemming [69] Text cleaning, tokenization, stemming, negation detection [70]…”
Section: Referencementioning
confidence: 99%
“…The tweets and reviews used for sentiment analysis often contain noise in the form of words that do not contribute towards the classification and hence pre-processing is an important task in sentiment analysis. For example, research [19] employs sentiment analysis on Arabic tweets. The impact of stemming, feature correlation, and n-grams model is thoroughly investigated in Arabic text.…”
Section: Research Work On the Pre-processing In Sentiment Analysismentioning
confidence: 99%
“…The recent studies (Aldayel & Azmi, 2016;Asghar, Ahmad, Qasim, Zahra, & Kundi, 2016;Duwairi & El-Orfali, 2014;Ikeda, Takamura, Ratinov, & Okumura, 2008) have demonstrated that their sentiment update methods produce promising results with respect to accurate scoring of domainspecific words in the sentiment analysis of user reviews. They achieved significant improvement in accuracy in both the hotel and movie domains.…”
Section: Updating a Term's Sentiment Scorementioning
confidence: 99%